Kant on the Circularity of Appearance and the Thing-in-Itself as a Negative Noumenon - Oren, Yady (Con-Textos Kantianos. International Journal of Philosophy, 2026)
In the A-edition of the Critique of Pure Reason, Kant argues that the concept of appearance leads to circularity that necessitates the assumption of a thing-in-itself. This paper considers three readings, each of which follows a contemporaneously dominant approach to understanding the appearance-thing duality: the causal, the two-object, and the two-aspect interpretations. I show that the duality in this argument cannot be understood according to any of these interpretations. Instead, following less currently favored interpreters, I emphasize that the thing addressed in the argument is to be understood as a negative noumenon, which has the role of unifying the manifold sensible data into an object. I further argue that, from a historical perspective, Kant's reduction of the thing to its unifying function expresses his critique of both the empiricist and rationalist traditions. Finally, I suggest that the thing-appearance duality should be understood as between two functions inherent in cognition.
Keywords: Transcendental Idealism; Thing-in-itself; Circularity; Transcendental Object; Phenomena and Noumena